Comparison of in vivo and in vitro preimplantation embryo development in OXYS and WAG rats - V. V. Kozhevnikova; T. N. Igonina; E. Yu. Brusentsev; V. I. Mokrousova; E. A. Kizilova; I. N. Rozhkova; V. A. Naprimerov; S. Ya. Amstislavsky (Вавиловский журнал генетики и селекции)
OXYS rats are the model of precocious senescence. Numerous studies addressed physiology and behavior in rats of this strain during a postnatal period of their life, however, preimplantation development in OXYS rats has not yet been investigated. This study is addressing preimplantation embryonic development in OXYS rats both in vivo and in vitro. Rats of the WAG strain were used as controls. For studying the in vivo development, the embryos were collected from OXYS and WAG rats on day 5 post coitum, the stages of embryo development were estimated, the percentage of embryos at blastocyst stage and the cell numbers in these blastocysts were counted. In a special experiment, for studying in vitro development, the embryos were collected from both rat strains on day 4 post coitum and were cultured in vitro in P1 medium for 48 hours with or without supplementation with IGF-1 (200 ng/mL). Thereafter the percentage of embryos at blastocyst stage and the cell numbers in these blastocysts were counted in the same manner as for the in vivo experiment. This study reports that in vivo derived blastocysts of OXYS rats contain fewer cells on day 5 of their development than in vivo derived blastocysts of WAG rats. In vitro culture of the early preimplantation embryos in P1 medium mitigated the difference in the rate of embryo development between these two strains, the addition of IGF-1 into culture medium exerts neither negative nor positive effect on the rate of in vitro embryo development in rats of both strains.